The impact of population aging on the labor market: the case of Sri Lanka - Milan Vodopivec; Nisha Arunatilake (Institute for the Study of Labor (IZA), 2008)
Sri Lanka's population is predicted to age very fast during the next 50 years, bringing a slowdown of labor force growth and after 2030 its contraction. Based on an original, 2006 representative survey of old people in Sri Lanka conducted as a part of this study, the paper examines labor market consequences of this process, focusing on retirement pathways and the determinants of labor market withdrawal. The paper finds that a vast majority of Sri Lankan old workers are engaged in the informal sector, work long hours, and are paid less than younger workers. Moreover, as one of the first findings of its kind, the paper shows that labor market duality that characterizes most developing countries carries over to old age: (i) previous employment is the most important predictor of the retirement pathway; (ii) older workers fall into two categories: civil servants and formal private sector workers, who generally stop working before they reach 60 because they are forced to do so by mandatory retirement regulations, and casual workers and the self-employed, who are forced to work until very old age (or death) due to poverty and who stop working primarily because of poor health; and (iii) the option of part-time work is used primarily by workers who held regular jobs in their prime age employment, but not by casual workers and self-employed.
urn:nbn:de:101:1-20080421133
Keywords: J11; 330; Population aging; labor supply of old workers; labor demand for old workers; Arbeitsmarkt; Alternde Bevölkerung; Ältere Arbeitskräfte; Altersgrenze; Sri Lanka